Familial Hypercholesterolemia: Genetics, Symptoms, Diagnosis and Treatment - A Literature Overview - Rutkiewicz, Maciej; Przygodzka, Sabina; Gadżała, Katarzyna; Garbino, Karolina; Brudniak, Katarzyna; Szuścik, Antoni; Czyczerska, Magdalena (Quality in Sport, 2025)
Familial hypercholesterolemia is a genetic disorder of lipid management, especially LDL-C. It's inherited autosomal dominant in most cases. The illness is characterized by high, low-density lipoprotein cholesterol (LDL-C) levels. According to many researchers, the frequency of prevalence is estimated at 1:200 in the global population. Many studies showed that illness is underdiagnosed and therefore undertreated. There are three known genes coding three different proteins, and changes are in charge of wrong lipid management. These are: LDL-Receptor (LDLR), Apolipoprotein B (ApoB), and Proprotein convertase subtilisin/kexin 9 (PCSK9). People who are affected by mutation have around thirteen times higher risk of coronary artery disease (CAD) and, in order to that, premature death. Identifying sickness includes a physical examination, when we can observe xanthomas, corneal arcus, or xanthomata, and scales that focus on the patient's as well as his family's past. A definite diagnosis can be approved by genetic testing, which shows a causable mutation. The main goal in treatment therapy of familial hypercholesterolemia is to reduce the concentration of LDL-C in serum. First of all, patients should know what to do to reduce LDL-C levels. Education is critical for understanding the problem and creating a successful course. Moreover, it is necessary to quit smoking, increase physical activity, and reduce cholesterol, elevating products from diet such as saturated fats and alcohol. Weight reduction is recommended. In addition, pharmacological treatment must be performed. All individuals have statins implemented. In most cases, one drug isn't enough, so therapy containing ezetimib is common. Novel treatments, including monoclonal antibodies (mAb), antisense oligonucleotides (ASO), and PCSK9- inhibitors nowadays, are used with greater frequency and better results, providing higher efficiency in achieving targets.